2008
DOI: 10.1080/10640260802115829
|View full text |Cite
|
Sign up to set email alerts
|

Femininity and Eating Disorders

Abstract: The purpose of this study is to examine conformity to traditional feminine norms as a predictor of eating disorder (ED) symptomatology. Eight subscales of the Conformity to Feminine Norms Inventory (CFNI) were examined as predictors of ED symptomatology as assessed by the Eating Disorder Examination-Questionnaire (EDE-Q). Findings indicate the Thinness subscale of the CFNI predicted significant portions of the variance in ED symptomatology. Contrary to the findings of Mahalik and colleagues (2005), no other CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…The instrument has been used to examine its relationships with eating disorders and other clinical outcomes (Green, Davids, Skaggs, Riopel, & Hallengren, 2008;Hurt et al, 2007;Mahalik et al, 2005).…”
Section: Drafting the Original Questionnaire On The American Populationmentioning
confidence: 99%
“…The instrument has been used to examine its relationships with eating disorders and other clinical outcomes (Green, Davids, Skaggs, Riopel, & Hallengren, 2008;Hurt et al, 2007;Mahalik et al, 2005).…”
Section: Drafting the Original Questionnaire On The American Populationmentioning
confidence: 99%
“…According to the American Psychological Association's () Guidelines for psychological practice with girls and women , increasing the knowledge of feminine norms is an important focus since women's gender role socialization can have deleterious implications for women's mental health, task performance, and aspirations. In line with this aim to increase the knowledge about feminine norms and their consequences, several studies have found feminine‐norm conformity to be associated with problems such as body dissatisfaction, eating disorders, depression, and poor physical health (e.g., Green, et al ., ; Mahalik et al ., ; Murnen & Smolak, ; Sánchez‐López et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In most societies, masculinity is valued higher than femininity and this imbalance in power generally leads to women having less control over their lives than men (Cuddy, Fiske & Glick, ; Parent & Moradi, ). Some of the negative consequences that have been associated with conformity to feminine norms are body dissatisfaction, eating disorders, depression, and poor physical health (Green, Davids, Skaggs, Riopel & Hallengren, ; Mahalik et al ., ; Murnen & Smolak, ; Sánchez‐López, Cuéllar‐Flores & Dresch, ).…”
Section: Gender Role Theoriesmentioning
confidence: 99%
“…(i.e., White, middle and upper-class, heterosexual) ( Mahalik et al 2005, p. 418). Since its development the CFNI has become one of the standard measures of feminine norms, and has been used frequently in Canadian and US samples (Green et al 2008;Hurt et al 2007;Liss et al 2011;Moradi 2010, 2011;Smolak and Murnen 2008;Tokar et al 2007). Psychometric studies of translations of the CFNI in Slovakia (Lyócsa and Lyócsa 2013) and Spain (Sánchez-López and Cuéllar-Flores 2011; Sánchez-López et al 2012) have also been supportive of its use in those countries.…”
Section: The Conformity To Feminine Norms Inventorymentioning
confidence: 93%